RONC-15. CYSTIC DYNAMIC EVALUATION AND EARLY LATE TOXICITY IN TWO PEDIATRIC LOW GRADE GLIOMAS TREATED WITH ACTIVE SCANNING PROTON BEAM RADIOTHERAPY. Issue 2 (22nd June 2018) - Rombi, Barbara; Zucchelli, Mino; Vennarini, Sabina; Lipparini, Mirko; Micò, Soraia; Ammendolia, Ilario; Zama, Daniele; Prete, Arcangelo; Cammelli, Silvia; Toni, Francesco; Ronchi, Letizia; Morganti, Alessio G; et al.
Abstract: To evaluate cystic dynamics in two pediatric low grade gliomas during proton beam therapy (PBT) by weekly MRI and in the follow up (FU) time. Early late toxicity was also reported. Both solid and cystic tumor's components were drown in weekly MRI performed during proton radiation and in the FU phase. P1 case was a multiple partially resected 5 yo girl with hypothalamic pylocitic Astrocytoma no-responding after second line of chemotherapy, who acutely lost visual acuity due to cystic tumor's progression. P2 case was a 13 yo boy with progressive mesencephalic pylocitic Astrocytoma previously treated with multi-agents chemotherapy and several surgeries. After cystic drainage both were treated with PBT at 54 Gy GCE. During proton therapy # 7 MRI for P1 and # 6 MRI for P2 patient were performed and didn't shown cyst growth which required intervention; P1 developed two episodes of severe acute headache and both developed partial alopecia. In P1 patient both cystic and solid component progressively reduced (cyst/solid-1w +2/-15%, cyst/solid-2w -9/-22%, cyst/solid-3w -17/-28%, cyst/solid-4w -18/-38%, cyst/solid-5w -30/-43%, cyst/solid-6w -34/-44%, cyst/solid-1FU -43/-50%, cyst/solid-2FU -51/-63%). In P2 patient only cyst part progressively increased (cyst/solid-2w +7/-4%, cyst/solid-3w +36/-10%, cyst/solid-4w +58/-12%, cyst/solid-5w +73/-15%, cyst/solid-6w +90/-15%, cyst/solid-7w +94/-16%, cyst/solid-1FU +126/-37%, cyst/solid-2FU -18/-45%). P2 had transient cyst growth after PT with significant volume reduction on the second FU. After 10 months of median FU, no late side effects were noted however P1 improved visual acuity.